Analysis of Trends in the Development of Clusters in the Agro-Industrial Complex of Uzbekistan and the Current State of the System (Texas Journal of Agriculture and Biological Sciences, 2022)
In this article, it is known that agro-economic relations and agro-industrial markets play a special role in the development of the world economy. Therefore, it is important to analyze the indicators of targeted development of the agro-industrial sector on a large scale and regionally. The article analyzes the indicators of future development of the agro-industrial market of Uzbekistan and presents their clusters. The role of clusters in the agro-industry has also been studied by economists. The country has developed scientific findings and recommendations for further improvement of the agro-industrial sector.